A numerical study of auxetic composite panels under blast loadings - Imbalzano, Gabriele; Tran, Phuong; Ngo, Tuan D.; Lee, Peter V.S. (Composite structures, 2016)
Sandwich panels composed of auxetic cellular cores and metal facets are presented for blast resistance applications. The performance of this hybrid composite structure under impulsive loading is numerically studied, taking into account the rate-dependent effects. The Johnson–Cook law is used to model the behaviours of composite materials at high strain rates. Parametric analyses are performed to evaluate the performances of different designs of composite panels and compared with equivalent monolithic panels of identical areal masses in terms of deformations and dissipated plastic energy of the metal facets and auxetic crushable cores. Various design parameters are considered, including the auxetic unit cell effective Poisson’s ratio, material properties, thickness of facet, and diameter of the unit cell truss member. To reduce the computational time, a quarter of the panel is modelled with shell elements for the facets and beam elements for the core. In blast events, auxetic composite panels are found to effectively absorb double the amount of impulsive energy via plastic deformation, and reduce up to 70% of the back facet’s maximum velocity when compared with monolithic ones. The maximum back facet displacement is also noticeably reduced by up to 30% due to the densification and plastic deformation of the auxetic cores.